Preliminary analyses on measured received signals of orbiting RazakSAT satellite - Yaccop, Afham Abd Hakim; Yao, Yudong; Ismail, Ahmad Fadzil; Wan Nordin, Mimi Aminah; Badron, Khairayu (American Scientific Publishers, 2016)
RazakSAT satellite transmits both X-Band and S-band frequencies. The main objective of the whole research is to revise free space path attenuation. The preliminary findings in this study will contribute for final research works in the near future which includes the revision of free space path attenuation. Ultimately, a new and more reliable free space path loss formulation will be developed. In this particular study, the purpose is to find linear relationship between received signal from the satellite and the distance with the ground station. The second purpose is to derive linear relationship between the received signal and the elevation angle. As a start, S-band satellite data are selected for 3 months out of a year data samples. All satellite data samples for this study are filtered with rain gage data and weather radar data to ensure no rain and no cloud conditions. All derived linear formulations are presented in this paper.